2016
DOI: 10.1101/cshperspect.a028191
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathies

Abstract: NPHP-related ciliopathies (NPHP-RC) are a group of inherited diseases that affect genes encoding proteins that localize to primary cilia or centrosomes. With few exceptions, ciliopathies are inherited in an autosomal recessive manner, and affected individuals manifest early during childhood or adolescence. NPHP-RC are genetically very heterogeneous, and currently mutations in more than 90 genes have been described as single-gene causes. The phenotypes of NPHP-RC are very diverse, and include cystic-fibrotic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
350
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(358 citation statements)
references
References 194 publications
(150 reference statements)
6
350
2
Order By: Relevance
“…The phenotypes we observe following acute and partial depletion of giantin in mammalian cells (Asante et al, 2013) and zebrafish embryos (Bergen et al, 2017) are not seen following permanent loss of function of giantin. RCAN2 has been characterised as a negative regulator of Nuclear Factor of Activated T-cells (NFAT)-dependent transcriptional activation by calcineurin (Cao et al, 2002;Loh et al, 1996). Calcineurin also activates Transcription Factor EB (TFEB) by a similar mechanism (Medina et al, 2015).…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypes we observe following acute and partial depletion of giantin in mammalian cells (Asante et al, 2013) and zebrafish embryos (Bergen et al, 2017) are not seen following permanent loss of function of giantin. RCAN2 has been characterised as a negative regulator of Nuclear Factor of Activated T-cells (NFAT)-dependent transcriptional activation by calcineurin (Cao et al, 2002;Loh et al, 1996). Calcineurin also activates Transcription Factor EB (TFEB) by a similar mechanism (Medina et al, 2015).…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
“…Defects in the formation and/or function of the cilium lead to a cohort of human diseases known as ciliopathies (Braun and Hildebrandt, 2016) which affect multiple tissues leading to problems with respiratory, kidney, and heart function as well as vision, hearing, and fertility. Cilia defects are also linked to obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The PCM harbors not only proteins important for microtubule nucleation 5 , but also regulators of the cell cycle and its checkpoints, in line with important roles for centrosomes in intracellular signaling 6 . Fully mature centrioles can also dock at the plasma membrane where they function as basal bodies for the formation of cilia and flagella 7 , and dysfunction of the basal body-ciliary apparatus gives rise to ciliopathies 8 . In recent years, much progress has been made towards understanding how centriole duplication and centrosome assembly are controlled, and how deregulation of these processes can contribute to human disease 1,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Ciliopathies are associated with diverse phenotypes affecting nearly every tissue and organ system (see Braun and Hildebrandt 2016). Ciliopathies such as Bardet – Biedl syndrome (BBS) and Alström syndrome (ALMS) present with pediatric obesity as a clinical feature.…”
Section: Introductionmentioning
confidence: 99%
“…BBS is rare and genetically heterogeneous. To date, mutations in 21 genes, BBS1 – 21, have been identified that contribute to the development of the phenotype (see Braun and Hildebrandt 2016). Many BBS gene products form a large protein complex termed the BBSome (Nachury et al 2007).…”
Section: Introductionmentioning
confidence: 99%